Attitudes of health sciences students regarding euthanasia - Aritonović, Nemanja; Stojanović, Goran; Terzić, Negra; Jovčić, Ljiljana (Education and Research in Health Sciences, 2025)
Introduction: In the time of medical progress, euthanasia is still one of the most controversial topics today, being the target of numerous discussions and disagreements. The opinions of numerous experts in the fields of medicine, philosophy, psychology, law and on the other hand, the religious community as a whole are intertwined. Nurses are involved in the daily care of terminal patients, and may face difficult decisions such as euthanasia. Therefore, it is important to assess their attitudes and prepare them for such situations in their professional life. The aim of the paper: To examine the attitudes of students of health sciences regarding euthanasia.......................................Respondents: Students of bachelor cycle of applied studies in health sciences. .Methods: Descriptive and observational indirect method –questionnaire........................................Results with discussion on the results: The attitudes of the students included in our research do not differ much from the attitudes of students and nurses of other researchers regarding euthanasia. By comparing our research with the work of other researchers, we can see that the negative attitude towards euthanasia is closely related to the degree of religiosity. Students employed in the health care sector have a more positive attitude regarding the legalization of euthanasia compared to unemployed students. Conclusion: The majority of students in all study programs express a positive attitude regarding the implementation of euthanasia in certain cases, mostly when it comes to patients who are on life support, as well as in those patients who suffer continuously severe pain. The attitudes of religious students and students employed in the health care sector are significantly different compared to unemployed and non-religious students. Looking at all the results of the research, we conclude that a larger proportion of students are not sufficiently familiar with euthanasia, which can be concluded based on the expressed opposite attitudes.
Keywords: euthanasia; nurse; ethics; students; palliative care